Knowledge, attitude and practice towards the application of point-of-care pharmacogenotyping service among community pharmacists in Malaysia / Nurbaiduri Rosli, Mohd Rahimi Muda and Nur Sabiha Md Hussin - Rosli, Nurbaiduri; Muda, Mohd Rahimi; Md Hussin, Nur Sabiha (Faculty of Pharmacy, 2023)
Point-of-care pharmacogenetic testing (POCT) is a method employed by hospitals and community pharmacies for the detection of a patient's genetic profile related with drug response variability. The pharmacogenetic POCT has contributed significantly to the optimization of individualised medication therapy for patients. This strategy is extensively utilised in community pharmacies throughout developed nations, although Malaysia has yet to adopt it. The purpose of this study was to evaluate the knowledge, attitude, and practice of community pharmacists on the use of pharmacogenetic POCT in clinical practice. A cross-sectional study was conducted using a web survey comprising 36 items, with a response rate of 9.17% from 52 community pharmacists. The majority of respondents, predominantly females aged 31 to 40, exhibited diverse educational backgrounds and years of pharmacy practice. The study revealed a substandard level of knowledge, as indicated by a median score of 1. Despite this, participants displayed a positive attitude and eagerness to implement pharmacogenetic POCT in community settings. Notably, a statistically significant correlation was observed between knowledge and age (p=0.020), highlighting the need for targeted educational programs and training on pharmacogenomic POCT and its clinical application. To facilitate the optimal integration of this service locally, it is imperative to prioritize educational initiatives that enhance the understanding and application of pharmacogenetic POCT among community pharmacists. Addressing this knowledge gap can potentially revolutionize medication therapy, fostering a more personalized and effective approach to patient care.